Where did drugs come from? - Swinney, David (Henry Stewart Talks, 2013)
Drug discovery strategies, How drugs were discovered, The paradox between empirical and hypothesis driven drug discovery, How drugs work/molecular mechanism of action is at the core of the paradox, Practical application of new knowledge